APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DI CV. MATAHARI DIGITAL PRINTING SEMARANG - Imam Husni Al Amin; Kristanto Kristanto (Jurnal Ilmiah Dinamika Teknik, 2014)
Quite a lot of employmen, and human activities related to computers and aided by computer. Just as in the process of printing of softcopy into hardcopy. So it appears the so-called digital printing business. By utilizing the internet facility, the business is expected to grow rapidly and create a good relationship between the company and the customers are often called CRM. To enhance the company's relationship with the customer in terms of printing documents, CRM Applications of Digital Printing at CV. Matahari Digital Printing in Semarang is expected to help enable customers to print documents more efficiently, and increase the number of customers and customer loyalty. With a web-based, will facilitate information, data, and services up to a short time. Keywords: Digital printing, CRM, web programing